Poznawcze i ideowe funkcje dialogu religijnego - Sztajer, Sławomir (Polskie Towarzystwo Religioznawcze, 2014)
Religious dialogue plays two fundamental functions: cognitive and ideological. The cognitive function involves the understanding of other religions, searching for common elements included in different religious traditions, and sometimes searching for a higher truth. The ideological function consists in using religious dialogue for attaining noncognitive, and sometimes also nonreligious, goals such as peacebuilding, assuring mutual respect, gaining control over a religious faith, or proselytizing. It can be argued that religious dialogue is predominantly an ideological endeavour and its cognitive dimension is subordinated to ideological goals. To a considerable degree, religious dialogue is oriented towards attaining nonreligious goals and is functional for many nonreligious social practices.
Keywords: dialog; funkcja poznawcza dialogu religijnego; funkcje ideowe dialogu religijnego